Pengaruh Variasi Persentase Reduksi pada Proses Pengerolan Panas terhadap Sifat Mekanik dan Struktur Mikro Baja Laterit - Paristiawan, Permana Andi; Puspasari, Vinda; Pramono, Andika Widya; Adjiantoro, Bintang (Jurnal Rekayasa Mesin, 2020)
Lateritic ore is one of the raw materials for the steel industry. Lateritic ore processed into laterite steel has more advantages than steel in the market. It has better tensile strength, hardness, corrosion resistance, and welding properties. Lateritic steel is made by performing a casting process. This research aims to investigate the effect of reduction percentage on mechanical properties and microstructure of the lateritic steel after the hot rolling process. The specimens were heated to austenitization temperature at 10000C for 1 hour before the rolling process. The reduction percentage varies by 10%, 15%, and 20%. Hardness and impact test was conducted using a Rockwell Hardness and Charpy method. The microstructure was observed using an optical microscope. The results showed the optimum hardness of 58 HRC in a hot rolling sample with 20% reduction. The highest impact strength of 46 Joule and ductile fracture took place in this sample. The microstructure of this sample showed a bainitic phase causing lower hardness.